Preparation method of palladium carbon catalyst for brivaracetam intermediate synthesis

The distribution of palladium was adjusted by two impregnation methods, and the activity and stability of palladium carbon catalysts in the synthesis of bovacetam intermediates were solved, achieving efficient catalyst preparation and product yield.

CN119303566APending Publication Date: 2025-01-14ZHEJIANG APELOA JIAYUAN PHARMA +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411333354.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The existing palladium carbon catalysts have low catalytic activity in the synthesis of bovacetam intermediates, low product yield, and uneven distribution of metal palladium on activated carbon support, resulting in poor catalyst stability.

Method used

The two-impregnation method is adopted, the first time is the low-concentration palladium salt acetone solution is used to immerse for a long time, and the second time is the high-concentration palladium salt solution and fumaric acrylic acid copolymer for a short time. The palladium is controlled by adjusting the composition and concentration of the impregnation solution. Evenly distributed to improve the activity and stability of the catalyst.

Benefits of technology

The high activity and stability of palladium carbon catalysts are achieved, the synthesis efficiency and product yield of bovacetam intermediates are improved, and the long-term use effect of the catalyst is ensured.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the field of catalysts, and provides a preparation method of a palladium carbon catalyst for brivaracetam intermediate synthesis, and the preparation method comprises the following steps: dispersing pretreated active carbon in an impregnation liquid I, stirring for 8-16 hours, filtering, washing, and roasting to obtain a catalyst precursor I; the impregnation liquid I is a palladium salt acetone solution with palladium ion concentration of 4-8wt%; dispersing the catalyst precursor I in the steeping liquor II, stirring at normal temperature for 1-5 hours, filtering, washing and roasting to obtain a catalyst precursor II; the impregnation liquid II is a mixture of a fumaric acid-acrylic acid copolymer and a palladium salt aqueous solution with the palladium ion concentration of 10-20wt%; and reducing the catalyst precursor II to obtain the palladium carbon catalyst. The first impregnation adopts a low-concentration palladium salt acetone solution for long-time impregnation; the second-time impregnation adopts a high-concentration palladium salt aqueous solution and a fumaric acid-acrylic acid copolymer for normal-temperature short-time impregnation; the obtained palladium-carbon catalyst has high activity and good stability when being used for brivaracetam intermediate synthesis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of catalysts, and in particular to a method for preparing a palladium-carbon catalyst for synthesizing a brivaracetam intermediate. Background Art

[0002] (R)-4-Propylpyrrolidin-2-one is a key intermediate in the synthesis of brivaracetam. (R)-4-Propylpyrrolidin-2-one can be obtained by catalytic hydrogenation of (R)-2-oxo-4-(propyl-1-enyl)pyrrolidine-3-carboxylate to (R)-2-oxo-4-propylpyrrolidine-3-carboxylate, followed by decarboxylation.

[0003] The commonly used catalyst for catalytic hydrogenation is palladium carbon. When preparing palladium carbon, because there are many reducing groups such as aldehyde groups on the surface of activated carbon, it is easy to 2+ Reduced to metallic palladium Pd, the palladium metal solution is directly impregnated on the activated carbon carrier, and a metallic palladium film quickly appears on the surface of the activated carbon, resulting in only a small amount of metallic palladium microcrystals in the catalyst. Patent CN1436595 adds an oxidant to the impregnation solution to control the uniform distribution of metallic palladium on the surface of the carrier and prevent the carrier from directly reducing the metallic palladium compound during adsorption, so that the metallic palladium can be evenly distributed on the outer surface of the activated carbon carrier. However, when used to prepare (R)-4-propylpyrrolidone-2-one, there are still problems of low catalytic activity and low product yield. Therefore, an ideal solution is needed. Summary of the invention

[0004] The invention provides a method for preparing a palladium-carbon catalyst for synthesizing a brivaracetam intermediate. The first impregnation adopts a low-concentration palladium salt acetone solution for long-term impregnation; the second impregnation adopts a high-concentration palladium salt aqueous solution and a fumaric acid acrylic acid copolymer for short-term impregnation at room temperature; the obtained palladium-carbon catalyst has high activity when used for synthesizing a brivaracetam intermediate, and the catalyst has good stability.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions: The preparation method of the palladium-carbon catalyst for synthesizing the brivaracetam intermediate comprises the following steps: ① The first impregnation: the pretreated activated carbon is dispersed in the impregnation solution 1, stirred for 8-16 hours, filtered, washed and calcined to obtain a catalyst precursor 1; the impregnation solution 1 is a palladium salt acetone solution with a palladium ion concentration of 4-8wt%; ② Second impregnation: Disperse the catalyst precursor 1 in the impregnation solution 2, stir at room temperature for 1-5 hours, filter, wash and calcine to obtain the catalyst precursor 2; the impregnation solution 2 is a mixture of a fumaric acid acrylic acid copolymer and a palladium salt aqueous solution with a palladium ion concentration of 10-20wt%; ③ Reduction: The catalyst precursor is reduced to obtain a palladium-carbon catalyst.

[0006] Preferably, the preparation method of pre-treated activated carbon is: treating the activated carbon with acid and alkali in sequence. The acid treatment step is: soaking the activated carbon with 1-4 mol / L acid for 2-4 hours, filtering, washing the filter residue with water until neutral, and filtering to obtain solids. The alkali treatment step is: soaking the acid-treated activated carbon with 5-10% ammonia water for 10-20 minutes, filtering, washing the filter residue with water until neutral, and filtering to obtain solids.

[0007] Preferably, in step ①, the stirring temperature is 40-60°C.

[0008] Preferably, in the impregnation solution 1, the mass of palladium element in the palladium salt acetone solution is 5-10% of the mass of the activated carbon.

[0009] Preferably, in the second impregnation solution, the mass of the palladium element in the palladium salt aqueous solution is 0.2-1% of the mass of the activated carbon.

[0010] Preferably, in step ②, the mass of the fumaric acid acrylic acid copolymer is 0.05-5 times the mass of the palladium element.

[0011] Preferably, the fumaric acid acrylic acid copolymer is prepared by copolymerizing fumaric acid and acrylic acid in a mass ratio of 6-10:1 as monomers under the action of an initiator.

[0012] Preferably, the mass fraction of the monomer in the reaction system is 20-30%.

[0013] Preferably, the copolymerization temperature is 70-80°C.

[0014] Preferably, the initiator is sodium persulfate, and the amount used is 0.1-5 wt % of the monomer mass.

[0015] Preferably, vinyl chloride monomer is added during the polymerization of the fumaric acid acrylic acid copolymer: fumaric acid, acrylic acid and vinyl chloride are used as monomers in a mass ratio of 6-10:1:0.2-0.5, and copolymerization is carried out under the action of an initiator to obtain the copolymer.

[0016] Preferably, the calcination in step ① or ② is carried out at 200-300° C. for 2-5 hours.

[0017] Preferably, the reducing agent used for the reduction is formic acid, hydrazine hydrate or ascorbic acid.

[0018] Therefore, the beneficial effects of the present invention are as follows: the first impregnation uses a low-concentration palladium salt acetone solution for long-term impregnation, which is conducive to the uniform dispersion of palladium inside and outside the pores of the activated carbon, and this part of the palladium penetrates deeply and is not easy to be deactivated. After roasting and curing, the second impregnation is carried out, using a high-concentration palladium salt aqueous solution and a fumaric acid acrylic acid copolymer for short-term impregnation at room temperature. With the help of the copolymer, the palladium can be evenly distributed on the surface of the activated carbon, the particle size of this part of the palladium is relatively large, the catalytic activity is high, and it is connected with the copolymer and is not easy to fall off and deactivate. DETAILED DESCRIPTION

[0019] The technical solution of the present invention is further described below through specific embodiments.

[0020] In the present invention, unless otherwise specified, the raw materials and equipment used can be purchased from the market or are commonly used in the art. The methods in the embodiments, unless otherwise specified, are all conventional methods in the art. Unless otherwise specified, parts are all weight parts, temperatures are expressed in ° C or at ambient temperature, and pressures are atmospheric pressure or near atmospheric pressure. There are many variations and combinations of reaction conditions (such as component concentrations, desired solvents, solvent mixtures, temperatures, pressures, and other reaction ranges) and conditions that can be used to optimize the purity and yield of the product obtained by the method, and only reasonable routine experiments will be required to optimize such method conditions.

[0021] Example The preparation method of the palladium-carbon catalyst for synthesizing the brivaracetam intermediate comprises the following steps: (1) Pretreatment of activated carbon The activated carbon is treated with acid and alkali in sequence. The steps of acid treatment are: soak the activated carbon with 1-4 mol / L acid for 2-4h, the acid is hydrochloric acid, nitric acid or phosphoric acid; filter, wash the filter residue with water until neutral, and filter out the solid. Acid treatment can remove the ash (alkaline earth metals, heavy metal compounds, etc.) of the activated carbon and functionalize the surface of the carrier. The steps of alkali treatment are: soak the acid-treated activated carbon with 5-10% ammonia water for 10-20min, filter, wash the filter residue with water until neutral, and filter out the solid. Alkali treatment is conducive to the subsequent adsorption of palladium ions on the surface of activated carbon according to the precipitation mechanism. After ammonia treatment, the average particle size of the metal palladium on the surface of the activated carbon is smaller, and the Pd catalyst with -NH2-modified activated carbon as the carrier presents a higher metal dispersion than that modified with acidic oxygen-containing groups. The activated carbon can be any activated carbon in the prior art. In the embodiment, 50-60 mesh wood activated carbon is selected, and the specific surface area is 1000-2000m 2 / g, pore volume is 0.5-1mL / g.

[0022] (2) First impregnation The pretreated activated carbon is dispersed in the impregnation solution 1, heated to 40-60°C, kept warm and stirred for 8-16 hours, filtered, washed, and roasted at 200-300°C for 2-5 hours to obtain a catalyst precursor 1; the impregnation solution 1 is a palladium salt acetone solution with a palladium ion concentration of 4-8wt%, and the mass of the palladium element in the palladium salt acetone solution is 5-10% of the mass of the activated carbon. The palladium salt can be a palladium halide, acetate, nitrate or chloropalladic acid, preferably palladium chloride.

[0023] (3) Second impregnation The catalyst precursor 1 is dispersed in the impregnation solution 2, stirred at room temperature (i.e. without heating) for 1-5 hours, filtered, washed, and roasted at 200-300°C for 2-5 hours to obtain the catalyst precursor 2; the impregnation solution 2 is a mixture of a fumaric acid acrylic acid copolymer and a palladium salt aqueous solution with a palladium ion concentration of 10-20wt%, the mass of the palladium element in the palladium salt aqueous solution is 0.2-1% of the mass of the activated carbon, and the mass of the fumaric acid acrylic acid copolymer is 0.05-5 times the mass of the palladium element. The palladium salt can be a palladium halide, acetate, nitrate or chloropalladium acid, preferably palladium chloride.

[0024] The preparation method of the fumaric acid acrylic acid copolymer is as follows: using fumaric acid and acrylic acid in a mass ratio of 6-10:1 as monomers, dispersing the monomers in water, the mass fraction of the monomers being 20-30%, adding 0.1-5wt% of the mass of the monomer as an initiator sodium persulfate, heating to 70-80°C for insulation to carry out copolymerization to obtain the fumaric acid acrylic acid copolymer. Preferably, vinyl chloride monomer is also added during the polymerization of the fumaric acid acrylic acid copolymer: using fumaric acid, acrylic acid and vinyl chloride in a mass ratio of 6-10:1:0.2-0.5 as monomers, carrying out copolymerization under the action of the initiator to obtain the fumaric acid acrylic acid copolymer.

[0025] During the impregnation process, there are phenomena such as solute migration, diffusion and competitive adsorption, and palladium will produce various distribution conditions on the activated carbon. The distribution of palladium on the carrier can be controlled by adjusting the composition and concentration of the impregnation solution and the impregnation time. The first impregnation of the present invention uses a low-concentration palladium salt acetone solution and heats for a long time. After roasting and curing, the second impregnation is carried out, and a high-concentration palladium salt aqueous solution and fumaric acid acrylic acid copolymer are used for short-term impregnation at room temperature. ① In terms of solvent selection, water has a large polarity and acetone has a small polarity. When water is used as a solvent, the distribution of palladium on the activated carbon tends to be eggshell-type (i.e., mainly distributed on the surface), and when acetone is used as a solvent, the distribution of palladium on the activated carbon tends to be uniformly distributed (i.e., distributed inside and outside the pores). Therefore, acetone is used for the first impregnation to allow palladium to enter the pores. ② In terms of impregnation time, as the impregnation time increases, the distribution of palladium on the surface of the activated carbon gradually transitions from eggshell type to uniform type, so the first impregnation time is longer, allowing palladium to enter the pores. ③ In terms of the temperature of the impregnation solution, high temperature will accelerate the movement of molecules, which is conducive to the entry of palladium into the pores of activated carbon. However, too high temperature will reduce the adsorption efficiency, so the temperature needs to be controlled within a reasonable range. The first impregnation heating is to increase the probability of palladium entering the pores of activated carbon. ④ In terms of palladium concentration selection, too high palladium concentration is easy to obtain coarser metal particles and uneven particle size distribution, which is not easy to enter the micropores of activated carbon. Therefore, a low concentration of palladium salt solution is used in the first impregnation to make the adsorbed palladium evenly distributed in the micropores of activated carbon. In the second impregnation, the particle size obtained by high concentration is large, which is easier to approach the reactant and has high catalytic activity, and the particle size distribution is uneven, which increases the contact sites of the reactant. ⑤ Fumaric acid acrylic acid copolymer is also added in the second impregnation. On the one hand, the carboxyl group of fumaric acid acrylic acid copolymer will also be adsorbed on the surface of activated carbon, which has a competitive relationship with palladium ion adsorption, which can improve the dispersion uniformity of palladium; on the other hand, fumaric acid acrylic acid copolymer will chelate palladium ions, which can improve the binding force between palladium and activated carbon. After adding vinyl chloride monomer to the fumaric acid acrylic acid copolymer, chlorine is introduced, which has a beneficial effect on improving the dispersion uniformity of palladium.

[0026] In summary, the first impregnation of the present invention uses a low-concentration palladium salt acetone solution to heat and impregnate for a long time, which is conducive to the uniform dispersion of palladium inside and outside the pores of the activated carbon. This part of the palladium penetrates deeply and is not easy to be deactivated. After roasting and curing, the second impregnation is carried out, using a high-concentration palladium salt aqueous solution and a fumaric acid acrylic acid copolymer for short-term impregnation at room temperature. With the help of the copolymer, the palladium can be evenly distributed on the surface of the activated carbon. The particle size of this part of palladium is relatively large and easier to approach the reactant. The uneven particle size distribution increases the contact sites of the reactant, so the catalytic activity is high; and it is connected with the copolymer and is not easy to fall off and deactivate.

[0027] (4) Restore The catalyst precursor is reduced with a reducing agent to obtain a palladium carbon catalyst. The reduction step is not particularly limited, and conventional reduction operations are applicable. The reducing agent is preferably formic acid, hydrazine hydrate or ascorbic acid.

[0028] The palladium loading amount in the palladium carbon catalyst obtained by the invention is 5-8%.

[0029] Example 1 The preparation method of the palladium-carbon catalyst for the synthesis of the brivaracetam intermediate comprises the following steps: (1) Pretreatment of activated carbon The activated carbon was soaked in 3 mol / L hydrochloric acid for 3 hours, filtered, the filter residue was washed with water until neutral, and the solid was collected by suction. The solid was soaked in 8% ammonia water for 15 minutes, filtered, the filter residue was washed with water until neutral, and the solid was collected by suction to obtain pretreated activated carbon.

[0030] (2) First impregnation The pretreated activated carbon obtained in step (1) is dispersed in an impregnation solution 1, heated to 50°C, kept warm and stirred for 10 hours, filtered, washed, and calcined at 250°C for 4 hours to obtain a catalyst precursor 1. The impregnation solution 1 is a palladium chloride acetone solution with a palladium ion concentration of 6 wt%, and the mass of palladium element in the palladium chloride acetone solution is 8% of the mass of the activated carbon.

[0031] (3) Second impregnation The catalyst precursor 1 obtained in step (2) is dispersed in the impregnation liquid 2, stirred at room temperature for 4 hours, filtered, washed, and calcined at 250°C for 4 hours to obtain the catalyst precursor 2; the impregnation liquid 2 is a mixture of a fumaric acid acrylic acid copolymer and a palladium chloride aqueous solution with a palladium ion concentration of 15wt%, the mass of the palladium element in the palladium chloride aqueous solution is 0.6% of the mass of the activated carbon, and the mass of the fumaric acid acrylic acid copolymer is 1 times the mass of the palladium element.

[0032] The preparation method of the fumaric acid acrylic acid copolymer is as follows: fumaric acid and acrylic acid in a mass ratio of 9:1 are used as monomers, the monomers are dispersed in water, the mass fraction of the monomers is 25%, 1wt% of the initiator sodium persulfate is added based on the mass of the monomers, and the mixture is heated to 80°C for insulation to carry out copolymerization reaction to obtain the fumaric acid acrylic acid copolymer.

[0033] (4) Restore The catalyst precursor II obtained in step (3) was prepared into a 0.06 g / mL slurry, and 2 mL of 85% (volume percentage) hydrazine hydrate solution was added dropwise, and stirring was continued for 2 hours. The reduced catalyst was filtered, washed with deionized water until neutral, and finally dried in air at room temperature, and the wet sample was sealed and stored.

[0034] Example 2 The preparation method of the palladium-carbon catalyst for the synthesis of the brivaracetam intermediate comprises the following steps: (1) Pretreatment of activated carbon The activated carbon was soaked in 1 mol / L hydrochloric acid for 4 hours, filtered, the residue was washed with water until neutral, and the solid was collected by suction. The solid was soaked in 5% ammonia water for 20 minutes, filtered, the residue was washed with water until neutral, and the solid was collected by suction to obtain pretreated activated carbon.

[0035] (2) First impregnation The pretreated activated carbon obtained in step (1) is dispersed in an impregnation solution 1, heated to 40°C, stirred for 16 hours, filtered, washed, and calcined at 200°C for 5 hours to obtain a catalyst precursor 1. The impregnation solution 1 is a palladium chloride acetone solution with a palladium ion concentration of 4wt%, and the mass of palladium element in the palladium chloride acetone solution is 10% of the mass of the activated carbon.

[0036] (3) Second impregnation The catalyst precursor 1 obtained in step (2) is dispersed in the impregnation liquid 2, stirred at room temperature for 1 hour, filtered, washed, and calcined at 200°C for 5 hours to obtain the catalyst precursor 2; the impregnation liquid 2 is a mixture of a fumaric acid acrylic acid copolymer and a palladium chloride aqueous solution with a palladium ion concentration of 10wt%, the mass of the palladium element in the palladium chloride aqueous solution is 0.2% of the mass of the activated carbon, and the mass of the fumaric acid acrylic acid copolymer is 0.05 times the mass of the palladium element.

[0037] The preparation method of the fumaric acid acrylic acid copolymer is as follows: fumaric acid and acrylic acid in a mass ratio of 6:1 are used as monomers, the monomers are dispersed in water, the mass fraction of the monomers is 30%, 0.1wt% of the initiator sodium persulfate is added based on the mass of the monomers, and the mixture is heated to 70°C for insulation to carry out copolymerization reaction to obtain the fumaric acid acrylic acid copolymer.

[0038] (4) Restore The catalyst precursor II obtained in step (3) was prepared into a 0.06 g / mL slurry, and 2 mL of 85% (volume percentage) hydrazine hydrate solution was added dropwise, and stirring was continued for 2 hours. The reduced catalyst was filtered, washed with deionized water until neutral, and finally dried in air at room temperature, and the wet sample was sealed and stored.

[0039] Example 3 The preparation method of the palladium-carbon catalyst for the synthesis of the brivaracetam intermediate comprises the following steps: (1) Pretreatment of activated carbon The activated carbon was soaked in 4 mol / L hydrochloric acid for 2 hours, filtered, the residue was washed with water until neutral, and the solid was collected by suction. The solid was soaked in 5% ammonia water for 20 minutes, filtered, the residue was washed with water until neutral, and the solid was collected by suction to obtain pretreated activated carbon.

[0040] (2) First impregnation The pretreated activated carbon obtained in step (1) is dispersed in an impregnation solution 1, heated to 60°C, stirred for 8 hours, filtered, washed, and calcined at 300°C for 2 hours to obtain a catalyst precursor 1. The impregnation solution 1 is a palladium chloride acetone solution with a palladium ion concentration of 8 wt%, and the mass of palladium element in the palladium chloride acetone solution is 10% of the mass of the activated carbon.

[0041] (3) Second impregnation The catalyst precursor 1 obtained in step (2) is dispersed in the impregnation liquid 2, stirred at room temperature for 5 hours, filtered, washed, and calcined at 300°C for 2 hours to obtain the catalyst precursor 2; the impregnation liquid 2 is a mixture of a fumaric acid acrylic acid copolymer and a palladium chloride aqueous solution with a palladium ion concentration of 20wt%, the mass of the palladium element in the palladium chloride aqueous solution is 1% of the mass of the activated carbon, and the mass of the fumaric acid acrylic acid copolymer is 5 times the mass of the palladium element.

[0042] The preparation method of the fumaric acid acrylic acid copolymer is as follows: fumaric acid and acrylic acid in a mass ratio of 10:1 are used as monomers, the monomers are dispersed in water, the mass fraction of the monomers is 30%, 5wt% of the initiator sodium persulfate is added based on the mass of the monomers, and the mixture is heated to 80°C for copolymerization to obtain the fumaric acid acrylic acid copolymer.

[0043] (4) Restore The catalyst precursor II obtained in step (3) was prepared into a 0.06 g / mL slurry, and 2 mL of 85% (volume percentage) hydrazine hydrate solution was added dropwise, and stirring was continued for 2 hours. The reduced catalyst was filtered, washed with deionized water until neutral, and finally dried in air at room temperature, and the wet sample was sealed and stored.

[0044] Example 4 The difference from Example 1 is that in step (2), the stirring is performed at room temperature without heating.

[0045] Example 5 The difference from Example 1 is that the amount of palladium added in step (2) and step (3) is interchanged, that is, the mass of the palladium element in the palladium chloride acetone solution in step (2) is 0.6% of the mass of the activated carbon, and the mass of the palladium element in the palladium chloride aqueous solution in step (3) is 8% of the mass of the activated carbon.

[0046] Example 6 The difference from Example 1 is that in step (3), the fumaric acid acrylic acid copolymer is added in excess, and the mass of the fumaric acid acrylic acid copolymer is 6 times the mass of the palladium element.

[0047] Example 7 The difference from Example 1 is that in step (3) of preparing the fumaric acid acrylic acid copolymer, the monomer ratio is not within the preferred range, and fumaric acid and acrylic acid are used as monomers in a mass ratio of 12:1.

[0048] Example 8 The difference from Example 1 is that vinyl chloride monomer is also added during the preparation of the fumaric acid acrylic acid copolymer in step (3), with fumaric acid, acrylic acid and vinyl chloride as monomers in a mass ratio of 9:1:0.3. The details are as follows: Fumaric acid, acrylic acid and vinyl chloride in a mass ratio of 9:1:0.3 are used as monomers, the monomers are dispersed in water, the mass fraction of the monomers is 25%, 1wt% of the initiator sodium persulfate is added based on the mass of the monomers, and the mixture is heated to 80°C for copolymerization to obtain a fumaric acid acrylic acid vinyl chloride copolymer.

[0049] Comparative Example Comparative Example 1 The difference from Example 1 is that the second impregnation is not performed. Specifically: The preparation method of the palladium-carbon catalyst for the synthesis of the brivaracetam intermediate comprises the following steps: (1) Pretreatment of activated carbon The activated carbon was soaked in 3 mol / L hydrochloric acid for 3 hours, filtered, the filter residue was washed with water until neutral, and the solid was collected by suction. The solid was soaked in 8% ammonia water for 15 minutes, filtered, the filter residue was washed with water until neutral, and the solid was collected by suction to obtain pretreated activated carbon.

[0050] (2) Impregnation The pretreated activated carbon obtained in step (1) is dispersed in an impregnation solution, heated to 50°C, kept warm and stirred for 10 hours, filtered, washed, and calcined at 250°C for 4 hours to obtain a catalyst precursor. The impregnation solution is a palladium chloride acetone solution with a palladium ion concentration of 6wt%, and the mass of palladium element in the palladium chloride acetone solution is 8% of the mass of the activated carbon.

[0051] (3) Restore The catalyst precursor obtained in step (2) was prepared into a 0.06 g / mL slurry, and 2 mL of 85% (volume percentage) hydrazine hydrate solution was added dropwise, and stirring was continued for 2 hours. The reduced catalyst was filtered, washed with deionized water until neutral, and finally dried in air at room temperature, and the wet sample was sealed and stored.

[0052] Comparative Example 2 The difference from Example 1 is that the first impregnation is not performed. Specifically: The preparation method of the palladium-carbon catalyst for the synthesis of the brivaracetam intermediate comprises the following steps: (1) Pretreatment of activated carbon The activated carbon was soaked in 3 mol / L hydrochloric acid for 3 hours, filtered, the filter residue was washed with water until neutral, and the solid was collected by suction. The solid was soaked in 8% ammonia water for 15 minutes, filtered, the filter residue was washed with water until neutral, and the solid was collected by suction to obtain pretreated activated carbon.

[0053] (2) Impregnation The pretreated activated carbon obtained in step (1) is dispersed in an impregnation liquid, stirred at room temperature for 4 hours, filtered, washed, and calcined at 250°C for 4 hours to obtain a catalyst precursor; the impregnation liquid is a mixture of a fumaric acid acrylic acid copolymer and a palladium chloride aqueous solution with a palladium ion concentration of 15wt%, the mass of the palladium element in the palladium chloride aqueous solution is 0.6% of the mass of the activated carbon, and the mass of the fumaric acid acrylic acid copolymer is 1 times the mass of the palladium element.

[0054] The preparation method of the fumaric acid acrylic acid copolymer is as follows: fumaric acid and acrylic acid in a mass ratio of 9:1 are used as monomers, the monomers are dispersed in water, the mass fraction of the monomers is 25%, 1wt% of the initiator sodium persulfate is added based on the mass of the monomers, and the mixture is heated to 80°C for insulation to carry out copolymerization reaction to obtain the fumaric acid acrylic acid copolymer.

[0055] (4) Restore The catalyst precursor was prepared into a 0.06 g / mL slurry, 2 mL of 85% (volume percentage) hydrazine hydrate solution was added dropwise, and stirring was continued for 2 hours. The reduced catalyst was filtered, washed with deionized water until neutral, and finally dried in air at room temperature, and the wet sample was sealed and stored.

[0056] Comparative Example 3 The difference from Example 1 is that the palladium chloride acetone solution in step (2) is replaced by a palladium chloride aqueous solution.

[0057] Comparative Example 4 The difference from Example 1 is that the stirring time in step (2) is shorter, which is 6 hours.

[0058] Comparative Example 5 The difference from Example 1 is that the palladium ion concentration of the impregnation solution 1 in step (2) is relatively high, that is, a palladium chloride acetone solution with a palladium ion concentration of 10 wt%.

[0059] Comparative Example 6 The difference from Example 1 is that the palladium ion concentration of the second impregnation solution in step (3) is relatively low, being a palladium chloride aqueous solution with a palladium ion concentration of 8 wt %.

[0060] Comparative Example 7 The difference from Example 1 is that no fumaric acid acrylic acid copolymer is added to the second impregnation solution in step (3).

[0061] Performance Testing The palladium-carbon catalyst of each embodiment and comparative example was subjected to a catalytic test, and the method was as follows: 10 g of (4R)-2-oxo-4-((E)-prop-1-en-1-yl)pyrrolidine-3-carboxylic acid methyl ester, 0.2 g of palladium-carbon catalyst and 50 mL of methanol were added to a hydrogenation kettle, the air was replaced with hydrogen 3 times, the hydrogenation reaction was stirred at 0.3 MPa for 3 h, the reaction was filtered after completion, the filtrate was concentrated to dryness under reduced pressure, and (R)-2-oxo-4-propylpyrrolidine-3-carboxylic acid methyl ester was obtained by purification by silica gel column chromatography. The reaction conditions were the same when applied. The results are shown in the following table. Conversion Rate % Conversion rate after 10 applications (%) The conversion rate decrease after 10 applications (%) Example 1 94.0 91.9 2.2 Example 2 93.8 91.5 2.4 Example 3 93.6 91.2 2.6 Example 4 91.3 87.8 3.8 Example 5 90.6 86.0 5.1 Example 6 92.4 89.2 3.5 Example 7 92.7 89.6 3.3 Example 8 94.9 93.0 2.0 Comparative Example 1 83.2 80.5 3.2 Comparative Example 2 84.0 76.7 8.7 Comparative Example 3 85.4 80.3 6.0 Comparative Example 4 86.9 83.9 3.5 Comparative Example 5 87.2 83.7 4.0 Comparative Example 6 88.1 85.0 3.5 Comparative Example 7 84.5 75.3 10.9 Commercially available 8% palladium carbon catalyst 81.3 71.1 12.6

[0062] As can be seen from the above table, compared with commercially available palladium-carbon catalysts, the palladium-carbon catalysts prepared in the embodiments of the present invention have excellent catalytic performance, and can still maintain a high conversion rate after being applied 10 times. Among them, embodiment 1 is the best embodiment. Compared with embodiment 1: In Example 4, the first impregnation was not heated, which was not conducive to the entry of palladium into the pores, resulting in a decrease in the palladium content in the pores. Therefore, the conversion rate decreased slightly, and the degree of decrease in the conversion rate after application was even greater. In Example 5, the palladium dosage in the two impregnations was opposite, with less dosage in the first time and more dosage in the second time. The distribution of palladium on the surface of activated carbon was mainly uniform for the first time, and mainly eggshell type for the second time. Therefore, if the second dosage is large, most of the palladium will be adsorbed on the outside of the activated carbon, and the stability will be a little worse. In Example 6, the copolymer is excessive, which will clog the pores and reduce the catalytic activity. In Example 7, the monomers are not within the preferred range when preparing the copolymer, resulting in the synthesized copolymer having a molecular weight that is too high. When mixed with activated carbon, it may clog the pores and reduce the catalytic activity.

[0063] Comparative Example 1 only experienced the first impregnation, and did not undergo the second impregnation, and the activity decreased significantly. Comparative Example 2 did not undergo the first impregnation, but directly performed the second impregnation, and the stability decreased significantly. Comparative Example 3 also used an aqueous solution of palladium chloride for the first impregnation. Affected by polarity, the distribution of palladium on the surface of activated carbon tended to be eggshell-type when water was used as a solvent, and palladium was not easy to enter the gaps in the activated carbon, so the catalyst activity decreased. Comparative Example 4 had a shorter time for the first impregnation, and the distribution of palladium on the surface of activated carbon had not yet completely transitioned from eggshell type to uniform type. Comparative Example 5 had a high palladium concentration in the first impregnation, which easily resulted in coarser metal particles and uneven particle size distribution, which were not easy to enter the micropores of activated carbon. Comparative Example 6 had a low palladium concentration in the second impregnation, and the metal particles were small and uniform in size, which reduced the contact of the reactants. Comparative Example 7 did not add a copolymer during the second impregnation, and the binding force between palladium and activated carbon decreased, resulting in a significant decrease in stability; the catalytic activity also decreased, because the copolymer can also improve the dispersion uniformity of palladium.

[0064] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technician familiar with this profession can make some changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.

Claims

1. A method for preparing a palladium-carbon catalyst for synthesizing a buvacetam intermediate, characterized in that: The following steps are involved: ① The first impregnation: the pretreated activated carbon is dispersed in the impregnation solution 1, stirred for 8-16 hours, filtered, washed and calcined to obtain a catalyst precursor 1; the impregnation solution 1 is a palladium salt acetone solution with a palladium ion concentration of 4-8wt%; ② Second impregnation: Disperse the catalyst precursor 1 in the impregnation solution 2, stir at room temperature for 1-5 hours, filter, wash and calcine to obtain the catalyst precursor 2; the impregnation solution 2 is a mixture of a fumaric acid acrylic acid copolymer and a palladium salt aqueous solution with a palladium ion concentration of 10-20wt%; ③ Reduction: Reduce the catalyst precursor to obtain a palladium-carbon catalyst.

2. The method for preparing the palladium-carbon catalyst for synthesizing the buvacetam intermediate according to claim 1, characterized in that: In step ①, the temperature during stirring is 40-60°C.

3. The method for preparing the palladium-carbon catalyst for synthesizing the buvacetam intermediate according to claim 1, characterized in that: In the impregnation solution 1, the mass of palladium element in the palladium salt acetone solution is 5-10% of the mass of the activated carbon.

4. The method for preparing the palladium-carbon catalyst for synthesizing the buvacetam intermediate according to claim 1 or 3, characterized in that: In the second impregnation solution, the mass of palladium element in the palladium salt aqueous solution is 0.2-1% of the mass of the activated carbon.

5. The method for preparing the palladium-carbon catalyst for synthesizing the brivaracetam intermediate according to claim 1, characterized in that: In step ②, the mass of the fumaric acid acrylic acid copolymer is 0.05-5 times the mass of the palladium element.

6. The method for preparing the palladium-carbon catalyst for synthesizing the brivaracetam intermediate according to claim 1, characterized in that: The preparation method of the fumaric acid acrylic acid copolymer is as follows: fumaric acid and acrylic acid in a mass ratio of 6-10:1 are used as monomers, and copolymerization is carried out under the action of an initiator to obtain the copolymer.

7. The method for preparing the palladium-carbon catalyst for synthesizing the brivaracetam intermediate according to claim 6, characterized in that: The mass fraction of the monomer in the reaction system is 20-30%.

8. The method for preparing the palladium-carbon catalyst for synthesizing the buvacetam intermediate according to claim 6 or 7, characterized in that: The copolymerization temperature is 70-80°C.

9. The method for preparing the palladium-carbon catalyst for synthesizing the brivaracetam intermediate according to claim 6, characterized in that: Vinyl chloride monomer is also added during the polymerization of fumaric acid acrylic acid copolymer: fumaric acid, acrylic acid and vinyl chloride are used as monomers in a mass ratio of 6-10:1:0.2-0.5, and copolymerization reaction is carried out under the action of an initiator to obtain the copolymer.

10. The method for preparing the palladium-carbon catalyst for synthesizing the brivaracetam intermediate according to claim 1, characterized in that: The calcination in step ① or ② is: calcining at 200-300 ℃ for 2-5 hours.